1996
DOI: 10.1037/0735-7044.110.1.86
|View full text |Cite
|
Sign up to set email alerts
|

Detailed behavioral analysis of water maze acquisition under APV or CNQX: Contribution of sensorimotor disturbances to drug-induced acquisition deficits.

Abstract: A detailed behavioral analysis of water-maze acquisition showed that the N-methyl-D-aspartate (NMDA) antagonist NPC17742 and the muscarinic antagonist scopolamine caused sensorimotor disturbances in behaviors required for maze performances and that these correlated with acquisition impairments in both hidden and visible platform versions of the maze in male rats. Behavioral disturbances included thigmotaxic swimming, swimming over and deflecting off the platform, abnormal swim behavior, and hyperactivity. Rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
160
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(174 citation statements)
references
References 66 publications
14
160
0
Order By: Relevance
“…The results show that the effects of systemically administered MK-801 on spatial learning in the water maze task cannot be dissociated from motor and/or sensory disturbances. This supports the view that NMDA receptors probably contribute to, but seem not to be crucial for, spatial learning (Cain 1998;Cain et al 1996;Saucier et al 1996).…”
Section: Discussionsupporting
confidence: 87%
“…The results show that the effects of systemically administered MK-801 on spatial learning in the water maze task cannot be dissociated from motor and/or sensory disturbances. This supports the view that NMDA receptors probably contribute to, but seem not to be crucial for, spatial learning (Cain 1998;Cain et al 1996;Saucier et al 1996).…”
Section: Discussionsupporting
confidence: 87%
“…Thus, this behaviour would have severely lirnited the opportunity of the 'laive SC0 rats to spontaneously encounter the platform. which likely interfered with subsequent rnaze acquisition [6,25]. The Naive S C 0 group also had a greater number of platform contacts that were deflections and swimovers.…”
Section: 1 7 Visible Platform Search Timementioning
confidence: 99%
“…and combined muscarinic and serotonergic antagonism. The combination of a detailed behavioural analysis and NSP was chosen because it has proven useful in clarifying the role of some neurorransrnitter receptor populations in the field of learning and memory [1,4,6,28,29].…”
Section: 1 7 Visible Platform Search Timementioning
confidence: 99%
“…However, given the i.c.v. route of drug administration, there followed considerable debate, (i) as to the brain locus of these effects (hippocampal (CA and DG subfields) vs. extrahippocampal), and (ii) whether the watermaze deficit in these animals reflected a learning impairment or a non-specific disruption of sensorimotor or motivational aspects of task performance 27,30,31 . Furthermore, subsequent pharmacological experiments showed that AP5-treated rats could in fact solve the SRM watermaze task, if they had received watermaze pretraining in a different spatial environment prior to testing with the drug (the spatial upstairs/downstairs task) 32,38 .…”
Section: Nmdar Antagonists and Spatial Learningmentioning
confidence: 99%
“…In particular, the idea that LTP (or an LTP-like mechanism) in the hippocampus supports associative spatial memory formation (i.e. associating particular spatial locations within a cognitive map with particular events or outcomes or stimuli) has been widely accepted 26 , and has only rarely been questioned [27][28][29][30][31][32] . However, recent evidence from a novel genetically modified mouse line challenges the relationship between hippocampal LTP and long-term, associative spatial memory formation 33 .…”
Section: Synaptic Plasticity and Spatial Memory Formationmentioning
confidence: 99%